Far-infrared treatment of experimental sinusitis in rabbits: A pilot study - Ceylan, S.; Özdemir, Hüseyin; Aydın, Mehmet Şerif (Verduci Publisher, 2023)
OBJECTIVE: Thermal therapy has existed for thousands of years and dates back to ancient civilizations such as the Finns, Romans, ancient Chinese, American Indians, and Egyptians. Sun therapy is a form of natural Far Infrared Rays (FIR) thermal therapy. Far infrared rays are invisible rays with the longest wavelength of natural sunlight. However, sunbathing should only be done in moderation, as sunlight contains ultraviolet rays that can burn and damage the skin. More than 30 million people in Asia, Europe, and Australia receive Far Infrared Therapy with FIR lamps. They emit 2-25-micron wavebands. We aimed to investigate whether FIR therapy that uses a similar waveband improves sinusitis symptoms. MATERIALS AND METHODS: This study was conducted on 10 New Zealand rabbits of both sexes, 7-8 months old, with an average weight of 1.8-2.4 kg. They were divided into four study groups. Sinusitis was induced in rabbits by blocking the sinus ostium, whereas some were left as control. Far infrared treatment with an infra-sin device was given with or without antibiotics. Mucosal samples were evaluated microscopically regarding epithelial eruption, epithelial vacuolization, interstitial edema, vascular congestion, leukocyte infiltration, and mucosal thickening. RESULTS: We found clinical and histopathological improvements in rabbits with sinusitis on the right side of the nose, to which we applied FIR treatment with the device Infra-Sin. CONCLUSIONS: Our findings in this animal study led us to conclude that it would be beneficial to study the effects of FIR treatment on people with allergic rhinitis and sinusitis and to identify the optimal dosing, treatment duration, and intensity. To add to our findings, looking into whether FIR therapy can be used as an alternative to antibiotic treatment for human sinusitis is essential.
Keywords: Far Infrared Radiation (FIR); Infrasin; Sinusitis; Far-Infrared Treatment; Thermal Therapy; Rabbits With Experimental Sinusitis